The monstratio theologica of Adolphe Gesché. Fundamental-theological inspiration of his life´s works - García Mourelo, SDB, Santiago (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
At the same time several studies about the theologian of Leuven, Adolphe Gesché, disclose nuclear points of his theology: his systematic, depth and intuition, new roads are opened in theological reflection driven by his intuitions. This article aims to show the relationships, –implicit and explicit–, of the author with the Fundamental Theology. This, in epistemological questions –values, issues, and functions– and in the specific deployment of this epistemology showing, thus, inclusiveness –among Fundamental Theology and Dogmatic Theology– of his life’s work. An authentic monstratio theologica.
Keywords: Adolphe Gesché; Fundamental Theology; theological epistemology; body; flesh; corporeality